Genetic Criticism: Oxen of the Sun, Episode of Joyce’s Ulysses - Cuerva Cuevas, Tamara (Journal of Artistic Creation and Literary Research, 2025)
The terms “genetic criticism” may sound unfamiliar to us, but they are becoming a very trendy part of literature studies. Although it is true that the interest on genetic criticism is not as well spread in English speaking countries as it is in France, it is a field that is gaining more and more supporters every day. The paper begins with a brief introduction to the field by defining what genetic criticism is, and explaining a little bit of its history. The section summarizes the most important theoretical approaches taken in the subject. Finally, this introduction is followed by a specific commentary on Genetic Criticism as applied to James Joyce. The paper mentions the genetic work made on Joyce’s Finnegans Wake, because it is the most genetically studied of all Joyce’s works. However, I decided to focus my attention in the genetic study of the Oxen of the Sun, an important chapter in Joyce’s Ulysses.